Genome-Wide Identification and Expression Analysis of the Tubby-Like Protein Family in the Malus domestica Genome - Xu, Jia-Ning; Xing, Shan-Shan; Zhang, Zheng-Rong; Chen, Xue-Sen; Wang, Xiao-Yun (Frontiers in Plant Science, 2016)
Abstract Tubby-like proteins (TLPs), which have a highly conserved β-barrel tubby domain, have been found to be associated with some animal-specific characteristics. In the plant kingdom, more than 10 TLP family members were identified in Arabidopsis, rice and maize, and they were found to be involved in responses to stress. The publication of the apple genome makes it feasible to systematically study the TLP family in apple. In this investigation, 9 TLP encoding genes (TLPs for short) were identified. When combined with the TLPs from other plant species, the TLPs were divided into three groups (group A, B and C). Most plant TLP members in group A contained an additional F-box domain at the N-terminus. However, no common domain was identified other than tubby domain either in group B or in group C. An analysis of the tubby domains of MdTLPs identified three types of conserved motifs. Motif 1 and 2, the signature motifs in the confirmed TLPs, were always present in MdTLPs, while motif 3 was absent from group B. Homology modeling indicated that the tubby domain of most MdTLPs had a closed β barrel, as in animal tubby domains. Expression profiling revealed that the MdTLP genes were expressed in multiple organs and were abundant in roots, stems, and leaves but low in flowers. An analysis of cis-acting elements showed that elements related to the stress response were prevalent in the promoter sequences of MdTLPs. Expression profiling by qRT-PCR indicated that almost all MdTLPs were up-regulated at some extent under abiotic stress, exogenous ABA and H2O2 treatments in leaves and roots, though different MdTLP members exhibited differently in leaves and roots. The results and information above may provide a basis for further investigation of TLP function in plants.